Epidemiology, surgical intervention and management of nasal trauma in the acute phase- clinical study in a tertiary centre - Sharma, Kalpana; Kalita, Devasree; Barman, Dipjyoti (International Journal of Research in Medical Sciences, 2024)
Background: The anatomy and location of nose makes it prone to blunt trauma. Delayed treatment leads to secondary nasal deformities and chronic nasal obstruction with difficult day-to-day activities. Methods: Institution-based prospective study done on 140 patients with recent trauma of nose coming to department of ENT, Gauhati medical college and hospital from August 2022-July 2023 to study different types of nasal trauma, clinical presentation, initial conservative and surgical management. Ethical approval taken from institutional ethics committee. Results: Male: female ratio 1.8:1 with 34.2% in 21-30 age-group followed-by 11-20. Most-common mechanism being road-traffic-accidents (35.7%) followed-by self-fall (25.7%), presentation being nasal bleed (97.1%) controlled with anterior nasal packing (70%), followed by swelling of nose (95.7%). Lacerations (60%) of nasal alae or dorsum repaired, septal-hematoma (5%) incised drained and splinted. CSF-rhinorrhoea (11.5%) managed conservatively. The 74.2% with nasal-bone fracture, 4.8% presenting <6 hours emergency reduction done, 11.5% closed reduction, 6.7% septo-rhinoplasty with tragal, costal cartilage grafts under general-anaesthesia. Conclusions: Injury to nose is common in male adolescents and adults due to RTAs. Prompt intervention necessary to prevent complications. Epidemiological facts advocate public health measures including strict traffic-rules, improving sports practices, interpersonal relationships, prevention of alcohol-intake while driving.